Stimulasi Ekspresi Melalui Teknik Reinterpretasi dalam Pertunjukan Musik Seni - Djohan, Djohan; Tyasrinestu, Fortunata; Setiawan, Chriestian Denny (Institut Seni Indonesia Yogyakarta, 2021)
The purpose of this study is to proved that musik reinterpretation is the most important aspect for both musikians and audiences in enjoying art musik. This is because in recent years there has been a declined in album sales and the number of audience for performing arts musik. So that the efforts of musikians to reinterpret various art musik repertoires by presenting new perspectives and impressions which in turn are expected to increased interest in art musik. The concept of emotion from Mehrabian-Russell in Bakker (1977) is used to understand the mechanism of emotional responses experienced by the audience after being treated by the modification of musikal reinterpretation. Then measurements were designed based on Westbrook & Reilly's theory of consumer satisfaction in Atila and Fisun Yüksel (2008) to identify the emotional responses which is the main factor in audiences satisfaction after listening to the repertoire being played. Mixed methods were used through a case study approach and a one-group experimental design with post-treatment measurements (One-group posttest-only design). Musikians recorded Allemande from Suite No. 6 for Johann Sebastian Bach's cello through the first video in the original style and in the second video, interpreting it in a romantic sense. Some of the musikal elements manipulated were tempo, dynamics, timbre and musikians' gestures. After the audience watched the two videos, they filled out a questionnaire to find out the emotional responses such as 'happy', 'joyful', 'sad', and 'bored'. The results showed that 56.4% did not experience pleasure and excitement when watching the first video. Then 73.8% of viewers experienced the emotions of 'fun' and 'joy' when watching the second video. The conclusion shows that reinterpretation of a repertoire is important because it can bring new perspectives and impressions to attract attention and give satisfaction to the audience.